Precursor for polyanionic sodium ion battery positive electrode material and preparation method thereof

By using the solution preparation method of NaxMyHzOa(POb)c·mH2O precursor, the grinding problem of high crystalline solid precursors in the prior art is solved, and a positive electrode of polyanionic sodium ion battery with high purity, excellent electrochemical performance and low cost is achieved. Preparation of materials.

CN119503750APending Publication Date: 2025-02-25SHENZHEN JANAENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411462404.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

During the preparation of existing polyanionic sodium ion battery positive electrode materials, solid precursors such as high crystalline FePO4 or FeC2O4 are difficult to completely dissolve during the grinding process, resulting in phase separation and affecting electrochemical performance. At the same time, solid abrasion takes a long time, high energy consumption and high cost.

Method used

NaxMyHzOa(POb)c·mH2O precursor is used, which reacts with the transition metal source and the acid solution to form a water-soluble substance. After oxidation and reaction with phosphate, pyrophosphate, etc., it forms a long-range disordered amorphous structure, and is realized through solution preparation method. Precipitation and purification.

Benefits of technology

A polyanionic sodium ion battery positive electrode material with high phase purity, high compaction density, excellent electrochemical performance, low cost and wide system applicability is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503750A_ABST
    Figure CN119503750A_ABST
Patent Text Reader

Abstract

The invention discloses a precursor for a polyanionic sodium ion battery positive electrode material and a preparation method of the precursor. The chemical general formula of the precursor is NaxMyHzOa (POb) c.mH2O, wherein M is a transition metal element Fe and / or Mn; the relationship among x, y, z, a, b and c is x + 3y + z-2a + 5c-2b * c = 0, and the value range of m is greater than or equal to 0. The precursor for the polyanionic sodium ion battery positive electrode material and the preparation method thereof have the characteristics of high phase purity, high compaction density, excellent electrochemical performance, low cost and wide system applicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a precursor for a positive electrode material of a polyanion sodium ion battery and a preparation method thereof. Background Art

[0002] Polyanion-type sodium ion battery cathode materials have high structural stability, thermodynamic stability, excellent cycle stability and rate performance and have been favored by the market. At present, the polyanion-type material systems that are widely studied on the market include sodium iron pyrophosphate, sodium iron pyrophosphate, sodium vanadium phosphate, sodium vanadium fluorophosphate, etc., which are composed of alkali metal tetrahedrons, transition metal tetrahedrons / octahedrons, and anion tetrahedrons / trihedrons arranged in a common point / plane / line manner to form a three-dimensional framework structure.

[0003] At present, commercially available materials such as sodium iron pyrophosphate are synthesized using the solid phase method, which uses highly crystalline anhydrous FePO4, FeC2O4, etc. as transition metal precursor sources, combined with water-soluble sodium sources, phosphorus sources and carbon sources, and the preparation of the material is achieved through grinding, mixing, spray drying, sintering and other processes. However, it is difficult to completely dissolve highly crystalline solids such as FePO4 and FeC2O4 during the grinding process. They are often suspended in the solution as solid particles of tens to hundreds of nanometers. The solid particles contain tens of thousands of atoms. From a local point of view, the sodium, transition metals and phosphorus elements in the slurry are difficult to mix evenly, and the sintering process can easily lead to phase separation, affecting the electrochemical properties of the material. At the same time, the grinding process of highly crystalline solids such as FePO4 and FeC2O4 takes a long time, requires too high equipment parameters, has high energy consumption, and has a large process investment cost. Therefore, in order to obtain polyanionic materials with high phase purity and low manufacturing process costs, it is necessary to develop suitable precursors therefor. The precursors must contain the elements required for the prepared material and exist in an amorphous bonded state. Summary of the invention

[0004] The purpose of the present invention is to provide a precursor for a positive electrode material of a polyanion sodium ion battery and a preparation method thereof, which has the characteristics of high phase purity, high compaction density, excellent electrochemical performance, low cost and wide system applicability.

[0005] The present invention can be implemented by the following technical solutions: The invention discloses a precursor for a positive electrode material of a polyanion sodium ion battery, wherein the precursor has a chemical formula of Na x M y H z O a (PO b ) c ·mH 2 O; Among them, M is a transition metal element Fe and / or Mn; the relationships among x, y, z, a, b, and c are 1 < x ≤ 3, 2 ≤ y ≤ 3, 3 ≤ b ≤ 4, 0 < z ≤ 0.5, 0 < a ≤ 0.5, c = (-x - 3y - z + 2a) / (5 - 2b), and the value range of m is m ≥ 0.

[0006] Na x M y H z O a (PO b ) c ·mH 2 O precursor, the Na x M y (PO b ) c is the main element of the precipitate, with a relatively high content, while H z O a is adsorbed on the surface of Na x M y (PO b ) c to maintain the conservation of positive and negative charges of elements during the precipitation process, and its content is relatively low.

[0007] Another aspect of the present invention lies in protecting a method for preparing a precursor for a cathode material of a polyanionic sodium-ion battery, including the following steps: S1. Preparation of the precursor solution: Mix a transition metal source with an acid solution, adjust the pH of the solution to promote the dissolution of the transition metal, and generate a transparent solution; S2. Preparation of the pre-oxidized precursor solution: Add an oxidant to the above solution to oxidize the divalent metal ions in the solution to trivalent, and generate a pre-oxidized precursor solution; S3. Preparation of the Na x M y H z O a (PO b ) c ·mH 2 O precipitate: Add a phosphorus source and a sodium source to the above pre-oxidized precursor solution, and at the same time use an alkaline compound to adjust the pH of the solution, so that the transition metal ions in the solution form a Na x M y H z O a (PO b ) c ·mH 2 O precipitate; S4. Purification treatment: Separate the solid and liquid of the above precipitate, wash it, and obtain Na x My H z O a (PO b ) c ·mH 2 O precursor powder.

[0008] In the present invention, the precursor has a chemical formula of Na x M y H z O a (PO b ) c ·mH 2 O, which uses a transition metal source to react with an acid to form a water-soluble substance, which is then bonded to phosphorus-containing compounds such as phosphate and pyrophosphate under high pH conditions after oxidation, and then precipitated, separated from the solid and liquid, and washed to obtain the final product. The precursor is a long-range disordered amorphous structure formed by the mutual interlocking of transition metal iron or manganese ions, phosphate, pyrophosphate, hydrogen ions, hydroxides, and lattice water. The primary particle size is nanometer-scale, and the internal ion bonding is uniform. It is very easy to disperse by grinding. When mixed with other components, the dispersion state is relatively high. The polyanion material prepared after sintering has high crystallinity, high phase purity, and excellent electrochemical properties.

[0009] Further, in step S1, the pH range is ≤4. When the pH is ≥4, the transition metal source cannot be completely dissolved and is likely to remain in the precursor precipitate, affecting the mixing uniformity between ions and being unfavorable for preparing high-purity polyanion materials; in step S3, the pH range is ≥3.0, the purpose of which is to make the transition metal ions in the solution co-precipitate with phosphate, pyrophosphate, hydrogen ion, hydroxide, etc., with Na x M y H z O a (PO b ) c ·mH 2 O form, the precipitate has a disordered non-static structure, which is beneficial to the uniform distribution of elements in the subsequent material preparation process; when the pH is lower than 3.0, the precipitate cannot be completely precipitated, affecting the precursor yield.

[0010] Furthermore, in step S2, the molar amount of the added oxidant is 1.0 to 2.0 times the molar amount of the transition metal in the precursor solution. When the added amount is less than 1.0 times, the divalent transition metal in the solution is not sufficient to completely oxidize the precipitate, affecting the element ratio in the precipitate. When the added amount is higher than 2.0 times, excess oxidant will increase the investment cost.

[0011] Furthermore, in step S2, the oxidant is one or more of hydrogen peroxide, peracetic acid, ammonium persulfate, sodium hypochlorite, sodium percarbonate, sodium perborate, sodium permanganate, and chromic acid; its purpose is to oxidize the divalent transition metal ions in the solution so that they subsequently undergo a coprecipitation reaction with other anions in the solution.

[0012] Furthermore, in step S3, the phosphorus source is one or more of a phosphate compound, a pyrophosphate compound, metaphosphoric acid, sodium metaphosphate, phosphorus pentoxide, polyphosphoric acid, and sodium polyphosphate; the phosphate compound is one or more of phosphoric acid, sodium phosphate and its acid derivatives, and ammonium phosphate and its acid derivatives; the pyrophosphate compound is one or more of pyrophosphoric acid, sodium pyrophosphate and its acid derivatives, and ammonium pyrophosphate and its acid derivatives.

[0013] Furthermore, in step S3, the sodium source is an inorganic sodium-containing compound and / or an organic sodium-containing compound, the inorganic sodium-containing compound is one or more of sodium sulfate, sodium nitrate, and sodium chloride; the organic sodium-containing compound is one or more of sodium formate, sodium acetate, sodium citrate, sodium ascorbate, sodium carboxymethyl cellulose, sodium ethanol, and sodium phenol.

[0014] Furthermore, in step S3, the alkaline compound is a nitrogen-containing compound and / or a sodium-containing alkaline compound, the nitrogen-containing compound is one or more of ammonia water, aniline, and amines; the sodium-containing alkaline compound is one or more of sodium oxide, sodium citrate, sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium formate, and sodium acetate.

[0015] Further, in step S4, the solid-liquid separation method is one or more of centrifugation, filtration, filter pressing, and vacuum filtration, and the Na x M y H z O a (PO b ) c ·mH 2 One or a combination of two or more methods for quickly removing free moisture from the surface of O.

[0016] Further, in step S2, the transition metal source is one or more of a water-insoluble manganese source, a water-soluble manganese source, a water-insoluble iron source, and a water-soluble iron source; the water-insoluble manganese source is one or more of elemental manganese, manganese oxalate, manganese hydroxide, manganous anhydride, manganic anhydride, permanganic anhydride, manganese monoxide, manganese dioxide, manganese trioxide, and manganese tetraoxide; the water-soluble manganese source is one or more of manganese sulfate, manganese nitrate, manganese acetate, manganese chloride, manganese citrate, and manganese gluconate; the water-insoluble iron source is one or more of elemental iron, ferric oxalate, ferric oxide, ferrous oxide, ferric oxide, ferrous hydroxide, and ferric hydroxide; the water-soluble iron source is one or more of ferric sulfate, ferric chloride, ferric acetate, ferric citrate, ferric nitrate, ferric gluconate, and ammonium ferrous sulfate.

[0017] Furthermore, the acid solution is an inorganic acid and / or an organic acid; the acid solution is one or more of nitric acid, sulfuric acid, hydrochloric acid, perchloric acid, permanganic acid, hydrobromic acid, hydroiodic acid, sulfurous acid, phosphoric acid, oxalic acid, hydrofluoric acid, chromic acid, carbonic acid, silicic acid, nitrous acid, hydrosulfuric acid, hypochlorous acid, formic acid, acetic acid, propionic acid, citric acid, tartaric acid, malic acid, benzoic acid, salicylic acid, and succinic acid.

[0018] The present invention discloses a precursor for a positive electrode material of a polyanion sodium ion battery and a preparation method thereof, which has the following beneficial effects: First, high phase purity, Na x M y H z O a (PO b ) c ·mH 2 The transition metal, phosphate and pyrophosphate in the precursor are mixed evenly. When using it as a precursor to prepare polyanionic materials, only the sodium source and carbon source required for the ratio need to be supplemented. Since the sodium source and carbon source are both water-soluble raw materials, they can be obtained by Na x M y H z O a (PO b ) c ·mH 2 The pores in the O particles penetrate into the interior of the material, achieving uniform mixing between elements and achieving the preparation of highly uniform and high phase purity materials; Second, the compaction density is high, Na x M y H z O a (PO b ) c ·mH 2The elements in the O precursor bond with each other. When using this as a raw material to prepare polyanion materials, the elements bond with each other and grow. There is no need for long-distance diffusion between ions. Crystal nuclei can be formed in situ and epitaxial growth can be carried out. They melt to form dense single crystal particles. There are fewer pores between the crystals, the density is larger, and the compaction density is greatly improved. Third, the electrochemical performance is excellent, because Na x M y H z O a (PO b ) c ·mH 2 O The precursor elements are mixed with high uniformity, the prepared material has high crystallinity and phase purity, and the element occupancy and sodium ion diffusion channels in the crystal are arranged regularly and orderly, so it has excellent rate performance and high capacity performance; Fourth, low cost, Na x M y H z O a (PO b ) c ·mH 2 O can be prepared by using a cheap transition metal source, and its mixing with other ions can be achieved by acid dissolution, and a high-value polyanion material precursor can be precipitated by subsequent oxidation precipitation. In addition, the amorphous nature of the precursor and the uniformity of the elements make it possible to achieve uniform mixing of ions without using special grinding equipment or grinding for a long time by the equipment when preparing the polyanion material, which will greatly reduce grinding energy consumption and save manufacturing costs; Fifth, the system has wide applicability. There are many types of polyanion materials, including iron pyrophosphate / sodium manganese, iron pyrophosphate / sodium manganese, iron phosphate / sodium manganese, non-stoichiometric sodium iron / manganese phosphorus system and other materials. According to the type and content of different material elements, we can adjust the solution pH, the amount and type of raw materials added, and prepare different series of materials with Na x M y H z O a (PO b ) c ·mH 2 O precursor, so as to match the application of various high-performance polyanion materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 For the Na of Application Example 1 1.40 Fe 2.91 H 0.13 O 0.13 (PO 7.5 ) 4 ·2H 2Preparation of O precursor and Na 4 Fe 2.91 (PO 4 ) 2 P 2 O 7 Material SEM; Figure 2 For comparative example 1, anhydrous FePO 4 PrecursorPreparation of Na 4 Fe 2.91 (PO 4 ) 2 P 2 O 7 Materials SEM. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.

[0021] The invention discloses a precursor for a positive electrode material of a polyanion sodium ion battery, wherein the precursor has a chemical formula of Na x M y H z O a (PO b ) c ·mH 2 O; Wherein M is a transition metal element Fe and / or Mn; the relationship between x, y, z, a, b, and c is x+3y+z-2a+5c-2b×c=0, and the value range of m is m≥0.

[0022] Another aspect of the present invention is a method for preparing a precursor for a positive electrode material for a protected polyanion sodium ion battery, comprising the following steps: S1. Preparation of precursor solution: mixing a transition metal source with an acid solution, adjusting the pH of the solution, promoting the dissolution of the transition metal, and generating a transparent solution; S2. Preparation of a pre-oxidation precursor solution: adding an oxidant to the above solution to oxidize the divalent metal ions in the solution into trivalent metal ions to generate a pre-oxidation precursor solution; S3、Na x M y H z O a (PO b ) c ·mH 2 Preparation of O precipitation: Add phosphorus source and sodium source to the above pre-oxidation precursor solution, and use alkaline compounds to adjust the pH of the solution so that the transition metal ions in the solution form Na x My H z O a (PO b ) c ·mH 2 O precipitation; S4, purification treatment: the above precipitate is separated from the solid and liquid, washed to obtain the polyanion type sodium ion battery positive electrode material Na x M y H z O a (PO b ) c ·mH 2 O precursor powder.

[0023] Further, in step S1, the pH range is ≤4; and in step S3, the pH range is ≥3.0.

[0024] Furthermore, in step S2, the added molar amount of the oxidant is 1.0 to 2.0 times the molar amount of the transition metal in the precursor solution.

[0025] Furthermore, in step S2, the oxidant is one or more of hydrogen peroxide, peracetic acid, ammonium persulfate, sodium hypochlorite, sodium percarbonate, sodium perborate, sodium permanganate, and chromic acid.

[0026] Furthermore, in step S3, the phosphorus source is one or more of a phosphate compound, a pyrophosphate compound, metaphosphoric acid, sodium metaphosphate, phosphorus pentoxide, polyphosphoric acid, and sodium polyphosphate; the phosphate compound is one or more of phosphoric acid, sodium phosphate and its acid derivatives, and ammonium phosphate and its acid derivatives; the pyrophosphate compound is one or more of pyrophosphoric acid, sodium pyrophosphate and its acid derivatives, and ammonium pyrophosphate and its acid derivatives.

[0027] Furthermore, in step S3, the sodium source is an inorganic sodium-containing compound and / or an organic sodium-containing compound, the inorganic sodium-containing compound is one or more of sodium sulfate, sodium nitrate, and sodium chloride; the organic sodium-containing compound is one or more of sodium formate, sodium acetate, sodium citrate, sodium ascorbate, sodium carboxymethyl cellulose, sodium ethanol, and sodium phenol.

[0028] Furthermore, in step S3, the alkaline compound is a nitrogen-containing compound and / or a sodium-containing alkaline compound, the nitrogen-containing compound is one or more of ammonia water, aniline, and amines; the sodium-containing alkaline compound is one or more of sodium oxide, sodium citrate, sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium formate, and sodium acetate.

[0029] Further, in step S4, the solid-liquid separation method is one or more of centrifugation, filtration, filter pressing, and vacuum filtration, and the Na x M y H z O a (PO b ) c ·mH 2 One or a combination of two or more methods for quickly removing free moisture from the surface of O.

[0030] Further, in step S2, the transition metal source is one or more of a water-insoluble manganese source, a water-soluble manganese source, a water-insoluble iron source, and a water-soluble iron source; the water-insoluble manganese source is one or more of elemental manganese, manganese oxalate, manganese hydroxide, manganous anhydride, manganic anhydride, permanganic anhydride, manganese monoxide, manganese dioxide, manganese trioxide, and manganese tetraoxide; the water-soluble manganese source is one or more of manganese sulfate, manganese nitrate, manganese acetate, manganese chloride, manganese citrate, and manganese gluconate; the water-insoluble iron source is one or more of elemental iron, ferric oxalate, ferric oxide, ferrous oxide, ferric oxide, ferrous hydroxide, and ferric hydroxide; the water-soluble iron source is one or more of ferric sulfate, ferric chloride, ferric acetate, ferric citrate, ferric nitrate, ferric gluconate, and ammonium ferrous sulfate.

[0031] Furthermore, the acid solution is an inorganic acid and / or an organic acid; the acid solution is one or more of nitric acid, sulfuric acid, hydrochloric acid, perchloric acid, permanganic acid, hydrobromic acid, hydroiodic acid, sulfurous acid, phosphoric acid, oxalic acid, hydrofluoric acid, chromic acid, carbonic acid, silicic acid, nitrous acid, hydrosulfuric acid, hypochlorous acid, formic acid, acetic acid, propionic acid, citric acid, tartaric acid, malic acid, benzoic acid, salicylic acid, and succinic acid.

[0032] Example 1 This embodiment relates to a precursor for a positive electrode material of a polyanion sodium ion battery. The precursor has a general chemical formula of Na x M y H z O a (PO b ) c ·mH 2 O; wherein M is the transition metal element Fe; the relationship between x, y, z, a, b, and c is x+3y+z-2a+5c-2b×c=0, and the value range of m is m≥0.

[0033] The precursor was prepared by the following method: S1. Preparation of precursor solution: mixing a transition metal source with an acid solution, adjusting the solution pH to ≤ 4, promoting the dissolution of the transition metal, and generating a transparent solution; S2, preparation of pre-oxidation precursor solution: add an oxidant to the above solution, oxidize the divalent metal ions in the solution into trivalent, and generate a pre-oxidation precursor solution. Specifically, the added molar amount of the oxidant is 2.0 times the molar amount of the transition metal in the precursor solution; the oxidant is hydrogen peroxide or peracetic acid. Specifically, the transition metal source is a water-insoluble iron source or a water-soluble iron source; the water-insoluble iron source is elemental iron, ferrous oxalate, ferrous gluconate, or ammonium ferrous sulfate. The acid solution is nitric acid, sulfuric acid, hydrochloric acid, perchloric acid, permanganic acid, hydrobromic acid, hydroiodic acid, sulfurous acid, or succinic acid.

[0034] S3、Na x M y H z O a (PO b ) c ·mH 2 Preparation of O precipitation: Add phosphorus source and sodium source to the above pre-oxidation precursor solution, and use alkaline compounds to adjust the solution pH ≥ 3.0, so that the transition metal ions in the solution form Na x M y H z O a (PO b ) c ·mH 2 O precipitation. Specifically, the phosphorus source is a phosphate compound and a pyrophosphate compound. The phosphate compound is phosphoric acid, sodium phosphate and its acid derivatives; the pyrophosphate compound is pyrophosphoric acid, sodium pyrophosphate and its acid derivatives. The sodium source is an inorganic sodium-containing compound. The inorganic sodium-containing compound is sodium sulfate, sodium nitrate and sodium chloride. The alkaline compound is a nitrogen-containing compound and a sodium-containing alkaline compound. The nitrogen-containing compound is ammonia water and aniline; the sodium-containing alkaline compound is sodium oxide, sodium citrate, sodium formate and sodium acetate.

[0035] S4, purification treatment: the above precipitate is separated from the solid and liquid, washed to obtain the polyanion type sodium ion battery positive electrode material Na x M y H z O a (PO b ) c ·mH 2 O precursor powder. Specifically, the solid-liquid separation method is centrifugation or filtration.

[0036] Example 2 This embodiment relates to a precursor for a positive electrode material of a polyanion sodium ion battery. The precursor has a general chemical formula of Na x M y H z O a (PO b )c ·mH 2 O; wherein M is a transition metal element Mn; the relationship between x, y, z, a, b, and c is x+3y+z-2a+5c-2b×c=0, and the value range of m is m≥0.

[0037] The precursor was prepared by the following method: S1. Preparation of precursor solution: mixing a transition metal source with an acid solution, adjusting the solution pH to ≤ 4, promoting the dissolution of the transition metal, and generating a transparent solution; S2. Preparation of pre-oxidation precursor solution: add an oxidant to the above solution to oxidize the divalent metal ions in the solution into trivalent ions to generate a pre-oxidation precursor solution. Specifically, the added molar amount of the oxidant is 1.5 times the molar amount of the transition metal in the precursor solution; the oxidant is hydrogen peroxide, peracetic acid, sodium perborate, sodium permanganate, chromic acid. Specifically, the transition metal source is a water-insoluble manganese source and a water-soluble manganese source; the water-insoluble manganese source is elemental manganese, manganese oxalate, and manganese hydroxide; the water-soluble manganese source is hypochlorous acid, formic acid, acetic acid, propionic acid, citric acid, tartaric acid, malic acid, benzoic acid, salicylic acid, and succinic acid.

[0038] S3、Na x M y H z O a (PO b ) c ·mH 2 Preparation of O precipitation: Add phosphorus source and sodium source to the above pre-oxidation precursor solution, and use alkaline compounds to adjust the solution pH ≥ 3.0, so that the transition metal ions in the solution form Na x M y H z O a (PO b ) c ·mH 2 O precipitation. Specifically, the phosphorus source is metaphosphoric acid, sodium metaphosphate, phosphorus pentoxide, polyphosphoric acid, sodium polyphosphate. The sodium source is an organic sodium-containing compound, and the organic sodium-containing compound is sodium formate, sodium acetate, sodium citrate, and sodium ascorbate. The alkaline compound is a nitrogen-containing compound and a sodium-containing alkaline compound, and the nitrogen-containing compound is ammonia water, amines; the sodium-containing alkaline compound is sodium oxide, sodium citrate, and sodium carbonate.

[0039] S4, purification treatment: the above precipitate is separated from the solid and liquid, washed to obtain the polyanion type sodium ion battery positive electrode material Na x M y H z O a (PO b ) c ·mH2 O precursor powder. Specifically, the solid-liquid separation method is to use centrifugal force or gravity extrusion to achieve Na x M y H z O a (PO b ) c ·mH 2 O The free water on the surface is removed quickly.

[0040] Example 3 This embodiment relates to a precursor for a positive electrode material of a polyanion sodium ion battery. The precursor has a general chemical formula of Na x M y H z O a (PO b ) c ·mH 2 O; wherein M is a transition metal element Fe and Mn; the relationship between x, y, z, a, b, and c is x+3y+z-2a+5c-2b×c=0, and the value range of m is m≥0.

[0041] The precursor was prepared by the following method: S1. Preparation of precursor solution: mixing a transition metal source with an acid solution, adjusting the solution pH to ≤ 4, promoting the dissolution of the transition metal, and generating a transparent solution; S2. Preparation of pre-oxidation precursor solution: add an oxidant to the above solution to oxidize the divalent metal ions in the solution into trivalent ions to generate a pre-oxidation precursor solution. Specifically, the added molar amount of the oxidant is 1.0 times the molar amount of the transition metal in the precursor solution; the oxidant is hydrogen peroxide, peracetic acid, sodium permanganate, and chromic acid. Specifically, the transition metal source is a water-soluble manganese source and a water-soluble iron source; the water-soluble manganese source is manganese sulfate and manganese nitrate; the water-soluble iron source is ferric sulfate, ferric chloride, ferric acetate, ferric citrate, and ferric nitrate. The acid solution is formic acid, acetic acid, propionic acid, citric acid, tartaric acid, malic acid, benzoic acid, salicylic acid, and succinic acid.

[0042] S3、Na x M y H z O a (PO b ) c ·mH 2 Preparation of O precipitation: Add phosphorus source and sodium source to the above pre-oxidation precursor solution, and use alkaline compounds to adjust the solution pH ≥ 3.0, so that the transition metal ions in the solution form Na x M y H z O a (POb ) c ·mH 2 O precipitation. Specifically, the phosphorus source is a phosphate compound, polyphosphoric acid, sodium polyphosphate, and the phosphate compound is phosphoric acid. The sodium source is an inorganic sodium-containing compound and an organic sodium-containing compound. The inorganic sodium-containing compound is sodium sulfate, sodium nitrate, and sodium chloride; the organic sodium-containing compound is sodium formate, sodium acetate, sodium citrate, sodium ascorbate, etc. The alkaline compound is a nitrogen-containing compound, and the nitrogen-containing compound is ammonia water, aniline, and amine.

[0043] S4, purification treatment: the above precipitate is separated from the solid and liquid, washed to obtain the polyanion type sodium ion battery positive electrode material Na x M y H z O a (PO b ) c ·mH 2 O precursor powder. Specifically, the solid-liquid separation method is vacuum filtration, and Na is squeezed by centrifugal force or gravity. x M y H z O a (PO b ) c ·mH 2 O The free water on the surface is removed quickly.

[0044] Example 4 This embodiment relates to a precursor for a positive electrode material of a polyanion sodium ion battery. The precursor has a general chemical formula of Na x M y H z O a (PO b ) c ·mH 2 O; wherein M is a transition metal element Fe and Mn; the relationship between x, y, z, a, b, and c is x+3y+z-2a+5c-2b×c=0, and the value range of m is m≥0.

[0045] The precursor was prepared by the following method: S1. Preparation of precursor solution: mixing a transition metal source with an acid solution, adjusting the solution pH to ≤ 4, promoting the dissolution of the transition metal, and generating a transparent solution; S2. Preparation of pre-oxidation precursor solution: add an oxidant to the above solution to oxidize the divalent metal ions in the solution into trivalent ions to generate a pre-oxidation precursor solution. Specifically, the added molar amount of the oxidant is 1.3 times the molar amount of the transition metal in the precursor solution; the oxidant is sodium hypochlorite, sodium percarbonate, sodium perborate, sodium permanganate, and chromic acid. Specifically, the transition metal source is a water-insoluble manganese source and a water-soluble iron source; the water-insoluble manganese source is elemental manganese, permanganic anhydride, manganese monoxide, manganese dioxide, manganese trioxide, and manganese tetraoxide; the water-soluble iron source is ferrous sulfate, ferric chloride, and ferric acetate. The acid solution is hydrosulfuric acid, hypochlorous acid, formic acid, acetic acid, propionic acid, citric acid, tartaric acid, malic acid, benzoic acid, salicylic acid, and succinic acid.

[0046] S3、Na x M y H z O a (PO b ) c ·mH 2 Preparation of O precipitation: Add phosphorus source and sodium source to the above pre-oxidation precursor solution, and use alkaline compounds to adjust the solution pH ≥ 3.0, so that the transition metal ions in the solution form Na x M y H z O a (PO b ) c ·mH 2 O precipitation. Specifically, the phosphorus source is a pyrophosphate compound and polyphosphoric acid. The pyrophosphate compound is pyrophosphate, sodium pyrophosphate and its acid derivatives, ammonium pyrophosphate and its acid derivatives. The sodium source is an inorganic sodium-containing compound and an organic sodium-containing compound. The inorganic sodium-containing compound is sodium sulfate, sodium nitrate, and sodium chloride; the organic sodium-containing compound is sodium formate, sodium acetate, sodium citrate, sodium ascorbate, sodium carboxymethyl cellulose, sodium ethanol, and sodium phenol. The alkaline compound is a nitrogen-containing compound and a sodium-containing alkaline compound. The nitrogen-containing compound is ammonia water, aniline, and amines; the sodium-containing alkaline compound is sodium oxide, sodium citrate, sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium formate, and sodium acetate.

[0047] S4, purification treatment: the above precipitate is separated from the solid and liquid, washed to obtain the polyanion type sodium ion battery positive electrode material Na x M y H z O a (PO b ) c ·mH 2 O precursor powder. Specifically, the solid-liquid separation method is centrifugation, filter pressing, and Na is achieved by centrifugal force or gravity extrusion. x M y Hz O a (PO b ) c ·mH 2 One or a combination of two or more methods for quickly removing free moisture from the surface of O.

[0048] Application Example 1 Na 1.40 Fe 2.91 H 0.13 O 0.13 (PO 3.75 ) 4 ·2H 2 Preparation of O precursor and Na 4 Fe 2.91 (PO 4 ) 2 P 2 O 7 Synthesis and electrochemical properties of materials Step 1: Add water to high-purity atomized iron powder and sulfuric acid in a molar ratio of 2.91:1.2, and adjust the pH of the solution to 2.0 with sulfuric acid to completely dissolve the atomized iron powder to form a transparent light green solution; Step 2: adding hydrogen peroxide to the above solution to oxidize the divalent iron in the solution to trivalent iron, thereby generating a pre-oxidized precursor solution; Step 3: Add phosphoric acid and pyrophosphoric acid (the molar ratio of phosphoric acid to iron is 2:2.91; the molar ratio of pyrophosphoric acid to iron is 1:2.91) to the above precursor solution, mix well, then add sodium formate (the molar ratio of sodium acetate to iron is 1.40:2.91), and then slowly add sodium hydroxide to adjust the solution pH to 6.0, so that the transition metal ions and phosphorus-containing functional groups in the solution generate Na 1.40 Fe 2.91 H 0.13 O 0.13 (PO 3.75 ) 4 ·mH 2 O precipitation; Step 4: The above precipitate is centrifuged and washed to obtain the polyanion positive electrode material Na 1.40 Fe 2.91 H 0.13 O 0.13 (PO 3.75 ) 4 ·2H 2 O precursor powder.

[0049] Will Na 1.40 Fe 2.91 H 0.13 O 0.13 (PO 3.75 )4 ·2H 2 O precursor, sodium acetate and sucrose (the amount added is 0.2 times the molar amount of sodium acetate) are mixed with water and ground in a molar ratio of 1:2.6 for about 0.1 hours. Compared with the commercial anhydrous FePO4 precursor used in comparative example 1, the grinding energy consumption is greatly reduced, and the process cost is significantly reduced. When the solid particle size Dmax in the slurry is ≤50nm, the above slurry is spray-dried with an inlet air temperature of 300°C and an outlet air temperature of 90°C to remove moisture and obtain a dry precursor powder. Finally, the above precursor powder is calcined at 650°C for 12 hours in a nitrogen atmosphere, and Na is obtained after natural cooling. 4 Fe 2.91 (PO 4 ) 2 P 2 O 7 Material.

[0050] Figure 1 In the 1.40 Fe 2.91 H 0.13 O 0.13 (PO 3.75 ) 4 ·2H 2 NaO precursor preparation 4 Fe 2.91 (PO 4 ) 2 P 2 O 7 The SEM of the material shows a regular elliptical morphology, with small primary particles and densely packed particles with almost no obvious pores, indicating that the amorphous precursor melts and crystallizes during the sintering process, the grains grow larger in size, and grow inline with each other, forming a denser structure. In addition, the results in Table 1 show that the porosity and specific surface area of ​​the material are 1.2% and 3.2 m 2 / g, which is lower than that of the material prepared from the anhydrous FePO4 precursor in Comparative Example 1, indicating that the melting degree of the amorphous precursor is high during the sintering process, the particle growth densification degree is intensified, and the pore content and specific surface area are significantly reduced. Therefore, the material shows a large compaction density of 2.27g / cm 3 , better than Comparative Example 1.

[0051] Will Na 4 Fe 2.91 (PO 4 ) 2 P 2 O 7 Material , SurP, PVDF5130 are added in a mass ratio of 9.5:0.2:0.3 NMP mixing, use a high-speed homogenizer to mix the above materials evenly to form a black slurry with uniform color and high fluidity, OfThe black slurry was then coated on aluminum foil using a 150um four-sided preparation device, and the film was dried in a vacuum oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a punching machine, with metallic sodium as the counter electrode and 1 mol / L NaClO 4 EC+DEC (1:1 vol%) + 5% FEC was used as the electrolyte and the separator was a PP / PE / PP three-layer separator, which was assembled into a CR2016 button cell in a glove box.

[0052] The electrochemical performance test results in Table 1 show that Na 4 Fe 2.91 (PO 4 ) 2 P 2 O 7 The discharge capacity of the electrode at a rate of 0.1C (1C = 129 mAh / g) is 125.6 mAh / g, and the capacity utilization rate is close to its theoretical specific capacity, which is higher than the discharge capacity of 89.3 mAh / g in Comparative Example 1, indicating that the material has good crystallinity, high phase purity, and low defect content in the structure during the sintering process, which is consistent with the Na 1.40 Fe 2.91 H 0.13 O 0.13 (PO 3.75 ) 4 ·2H 2 O is related to the uniformity of ion distribution in the precursor. During the precipitation process of the precursor, the ions are interlocked with each other by weak interaction forces to form a uniform precipitate. In the subsequent preparation process of the polyanion material, this uniformity is maintained, which is conducive to the local nucleation and melting generation of the material during the sintering process. In addition, Table 1 shows that the capacity retention rate of the electrode at a rate of 10C is as high as 99.1% compared with 0.1C, which is better than 85.2% in Comparative Example 1. The reason is that on the one hand, the material has a higher phase purity, a lower content of vacancies and reverse dislocations in the structure, a coherent ion diffusion channel, a lower diffusion energy barrier, and excellent ion diffusion kinetics. On the other hand, the material has a lower porosity, a higher degree of melting, a close connection between particles, and a high electronic conductivity. The combined effect of the above two reasons enables the material to exhibit excellent rate performance. Finally, the electrode maintained a capacity of 99.4% after 1000 cycles at a 1C rate, with almost no attenuation. This is related to the smaller specific surface area of ​​the material. The smaller the specific surface area, the fewer side reactions between the material interface and the electrolyte under high voltage, the less dissolved elements at the material interface, and the higher the structural stability. On the other hand, it is related to the high phase purity of the material. The higher the phase purity of the material, the fewer impure phase grain boundaries, the more uniform the stress dispersion caused by volume expansion, and the integrity between crystals is effectively maintained during the cycle. In summary, Na 1.40 Fe 2.91 H0.13 O 0.13 (PO 3.75 ) 4 ·2H 2 NaO precursor 4 Fe 2.91 (PO 4 ) 2 P 2 O 7 The material has better electrochemical performance due to its higher phase purity.

[0053] Application Example 2 Na 2.43 Fe 1.79 Mn 1.12 H 0.04 O 0.04 (PO 3.75 ) 4 ·2H 2 Preparation of O precursor and Na 4 Fe 1.79 Mn 1.12 (PO 4 ) 2 P 2 O 7 Synthesis and electrochemical properties of materials Step 1: Fe 2 O 3 , Mn 2 O 3 , sulfuric acid and water were mixed in a ratio of 0.895:0.56:1.2, and sulfuric acid was used to adjust the solution pH to 1.0 to promote Fe 2 O 3 , Mn 2 O 3 The reaction produces a transparent brown-green solution; Step 2: adding hydrogen peroxide to the brown-green solution to oxidize the divalent iron in the solution to trivalent iron, thereby generating a pre-oxidized precursor solution; Step 3: Add sodium dihydrogen phosphate and sodium hydrogen pyrophosphate (sodium dihydrogen phosphate and Fe 2 O 3 The molar ratio of sodium hydrogen pyrophosphate to Fe is 2:0.895. 2 O 3 The molar ratio is 1:0.895), and then sodium acetate is added after mixing evenly (sodium acetate and Fe 2 O 3 The molar ratio is 2.43:0.895), and finally sodium carbonate is slowly added to adjust the pH of the solution to 6.5, so that the transition metal ions in the solution generate Na 2.43 Fe 1.79 Mn1.12 H 0.04 O 0.04 (PO 3.75 ) 4 ·mH 2 O precipitation; Step 4: The above precipitate is centrifuged and washed to obtain the polyanion positive electrode material Na 2.43 Fe 1.79 Mn 1.12 H 0.04 O 0.04 (PO 3.75 ) 4 ·2H 2 O precursor powder.

[0054] Will Na 2.43 Fe 1.79 Mn 1.12 H 0.04 O 0.04 (PO 3.75 ) 4 ·2H 2 O precursor, sodium acetate and citric acid (the amount added is 0.3 times the molar amount of sodium acetate) are mixed and ground with water in a molar ratio of 1:2.37 for about 0.25 hours, which is significantly shorter than that in comparative example 2, and the process cost is reduced. This is related to the Na 2.43 Fe 1.79 Mn 1.12 H 0.04 O 0.04 (PO 3.75 ) 4 ·2H 2 The O precursor itself is non-static and the bonding energy between ions is not high. The dispersion of particles can be achieved by simple grinding. When the solid particle size Dmax in the slurry is ≤30nm, the slurry is spray-dried with an inlet air temperature of 290°C and an outlet air temperature of 100°C to remove moisture and obtain a dry precursor powder. Finally, the precursor powder is calcined at 670°C for 8h in a nitrogen atmosphere, and Na is obtained after natural cooling. 4 Fe 1.79 Mn 1.12 (PO 4 ) 2 P 2 O 7 Material.

[0055] The results in Table 1 show that Na 4 Fe 1.79 Mn 1.12 (PO 4 ) 2 P 2 O 7The porosity and specific surface area of ​​the material are 1.5% and 2.7m 2 / g, which is much lower than the result of Comparative Example 2. This is related to the lower porosity of the material and the greater degree of melting between particles during sintering. 2.43 Fe 1.79 Mn 1.12 H 0.04 O 0.04 (PO 3.75 ) 4 ·2H 2 Due to its weak crystallization, the O precursor tends to spontaneously melt and densify during the subsequent high-temperature sintering process of material preparation, which has a significant regulatory effect on reducing the porosity and specific surface area of ​​the finished material. Finally, the material exhibits a high compaction density (2.23 g / cm 3 ).

[0056] Will Na 4 Fe 1.79 Mn 1.12 (PO 4 ) 2 P 2 O 7 The material, SurP, and PVDF5130 were mixed with NMP in a mass ratio of 9.5:0.2:0.3. The above materials were mixed evenly using a high-speed homogenizer to form a black slurry with uniform color and high fluidity. Then, a 150um four-sided preparation device was used to coat the black slurry on aluminum foil. The film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a punching machine. Metal sodium was used as the counter electrode, and 1 mol / L NaClO 4 EC+DEC (1:1 vol%) + 5% FEC was used as the electrolyte and the separator was a PP / PE / PP three-layer separator, which was assembled into a CR2016 button cell in a glove box.

[0057] The electrochemical performance test results in Table 1 show that the discharge capacity of the electrode is 121.4 mAh / g at a rate of 0.1C (1C = 129 mAh / g), and the capacity is better than that of Comparative Example 2. This is related to the higher phase purity and crystallinity of the material. The higher the phase purity of the material, the fewer defects in the crystal structure that hinder the transmission and diffusion of ions and electrons, and the more conducive to the high capacity of the material. In addition, Table 1 shows that the capacity retention rate of the electrode at a rate of 10C is as high as 98.4% compared with 0.1C, which is much higher than 79.2% in Comparative Example 2, indicating that the sodium ion diffusion barrier in the material structure is low and the ion conduction rate is fast. At the same time, because the porosity of the material is low, the particles are in close contact, and the electron transmission rate is also greatly improved, thereby reflecting excellent rate performance. Finally, the electrode retained 98.7% of its capacity after 1000 cycles at a 1C rate, and its cycle stability was excellent, indicating that the higher the phase purity of the material and the better the crystal integrity, the more uniform the force generated by the volume expansion of each crystal during the sodium extraction process, which can reduce the probability of structural powderization and improve the cycle stability. At the same time, the smaller specific surface area of ​​the material will also reduce its catalysis of the electrolyte under high pressure to a certain extent, thereby reducing the side reactions at the material interface and improving its cycle stability. In summary, based on Na 2.43 Fe 1.79 Mn 1.12 H 0.04 O 0.04 (PO 3.75 ) 4 ·2H 2 NaO precursor 4 Fe 1.79 Mn 1.12 (PO 4 ) 2 P 2 O 7 The material has better electrochemical performance due to its higher phase purity.

[0058] Comparative Example 1 Anhydrous FePO 4 Precursor preparation Na 4 Fe 2.91 (PO 4 ) 2 P 2 O 7 Materials and their electrochemical properties Anhydrous FePO4, phosphoric acid, sodium acetate were mixed with citric acid (the amount added was 0.2 times the molar amount of sodium acetate) in a molar ratio of 2.91:1.0:4.0 and ground for more than 10 hours. The grinding energy consumption was large and the efficiency was low. This was related to the high crystallinity of commercial anhydrous FePO4, which made it difficult to reduce the particle size during grinding. When the particle size of the solid particles in the slurry was Dmax≤50nm, the slurry was spray-dried with an inlet temperature of 300°C and an outlet temperature of 90°C to remove moisture and obtain a dry precursor powder. Finally, the above precursor powder was calcined at 650°C for 12 hours in a nitrogen atmosphere, and Na was obtained after natural cooling. 4 Fe 2.91 (PO 4 ) 2 P 2 O 7 Material.

[0059] Figure 2 Na 4 Fe 2.91 (PO 4 ) 2 P 2 O 7 The material SEM shows that the particles are elliptical and spherical, and the particles are composed of primary particles of about 50-200nm. The particles are interlocked with each other, leaving a large number of pores. The results in Table 1 show that the porosity and specific surface area of ​​the material are as high as 19.4% and 14.6m 2 / g, which is much higher than that of Application Example 1. This is related to the characteristics of the commercial anhydrous FePO4 precursor itself. The precursor is mostly a high-temperature sintering phase of about 700°C, with a high crystallinity and a large particle hardness. 4 Fe 2.91 (PO 4 ) 2 P 2 O 7 During the grinding process of the material precursor, the particle size of the anhydrous FePO4 precursor decreased significantly, but the grinding process did not improve the hardness of the particles much. During the subsequent sintering process, the highly crystalline nano-FePO4 precursor was difficult to melt with each other to form dense particles, resulting in a significant increase in its porosity and specific surface area, and a decrease in compaction density (1.56 g / cm 3 ).

[0060] Will Na 4 Fe 2.91 (PO 4 ) 2 P 2 O 7The material, SurP, and PVDF5130 were mixed with NMP in a mass ratio of 9.5:0.2:0.3. The above materials were mixed evenly using a high-speed homogenizer to form a black slurry with uniform color and high fluidity. Then, the black slurry was coated on aluminum foil using a 150um four-sided preparation device. The film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a punching machine. Metal sodium was used as the counter electrode and 1 mol / L NaClO 4 EC+DEC (1:1 vol%) + 5% FEC was used as the electrolyte and the separator was a PP / PE / PP three-layer separator, which was assembled into a CR2016 button cell in a glove box.

[0061] The results in Table 1 show that the material has a discharge capacity of only 89.3 mAh / g at a rate of 0.1C (1C = 129 mAh / g), which is lower than that in Application Example 1. The reduction in capacity is closely related to the phase purity of the material, and the phase purity is determined by the ion uniformity in the preparation process of the material precursor, indicating that the material prepared with anhydrous FePO4 as a precursor cannot be effectively and evenly mixed due to elements such as sodium, iron, and phosphorus, resulting in the final material containing impurities such as inactive sodium iron phosphate or low-capacity sodium iron pyrophosphate, which reduces the effective active ingredients of the material per unit mass, resulting in a decrease in the material capacity. In addition, Table 1 shows that the capacity retention rate of the electrode at a rate of 10C is only 85.2% compared with 0.1C, which is worse than that in Application Example 1. The reason is that on the one hand, more pores in the material hinder electronic conductivity, and on the other hand, the presence of impurities produces a large number of grain boundaries, which hinder the rapid conduction of ions between particles, ultimately resulting in a decrease in the capacity of the material at high rates. Finally, at 1C rate, after 1000 cycles, the capacity retention rate of the electrode was only 92.6%, with obvious attenuation. The reason is related to the high specific surface area of ​​the material. The higher the specific surface area, the more electrolyte decomposition sites there are at higher voltages, and the generated by-products have an adverse effect on the stability of the material interface structure. In addition, when the impurity phase contained in the material is deintercalated with sodium, its volume anisotropic expansion is very likely to produce microcracks between the main phase, resulting in continuous decomposition of the electrolyte, affecting the stability of the material structure. In summary, the anhydrous FePO 4 Na prepared from precursor 4 Fe 2.91 (PO 4 ) 2 P 2 O 7 The inhomogeneity of material reaction caused by low phase purity will accelerate the degradation of the electrochemical performance of the material.

[0062] Comparative Example 2 Anhydrous FePO 4 and Mn 2O 3 Precursor preparation Na 4 Fe 1.79 Mn 1.12 (PO 4 ) 2 P 2 O 7 Materials and their electrochemical properties Anhydrous FePO 4 , Mn 2 O 3 , sodium dihydrogen phosphate and citric acid (the amount added is 0.3 times the molar amount of sodium dihydrogen phosphate) are mixed with water and ground in a molar ratio of 1.79:0.56:4.0 for more than 15 hours. The grinding time is much longer than that of application example 2. The main reason is that anhydrous FePO 4 , Mn 2 O 3 The crystallinity is high, the crystal hardness is large, the grinding is difficult, the time is long, the efficiency is low, and the cost investment is high. When the particle size Dmax of the solid particles in the slurry is ≤30nm, the slurry is spray-dried, the air inlet temperature is 290°C, the air outlet temperature is 100°C, and the moisture is removed to obtain a dry precursor powder. Finally, in a nitrogen atmosphere, the above precursor powder is calcined at 670°C for 8h, and Na is obtained after natural cooling. 4 Fe 1.79 Mn 1.12 (PO 4 ) 2 P 2 O 7 Material.

[0063] The physical and chemical test data in Table 1 show that the porosity and specific surface area of ​​the material are 16.9% and 13.8 m 2 / g, much higher than that of Application Example 2, and its 2 O 3 The precursor has high crystallinity, large grain size, high crystal integrity, and is not easy to melt and shrink after sintering. The porosity content is high after the particles are stacked, the specific surface area is large, and the compaction density is reduced (1.68g / cm 3 ).

[0064] Will Na 4 Fe 1.79 Mn 1.12 (PO 4 ) 2 P 2 O 7 Material , SurP, PVDF5130 in a mass ratio of 9.5:0.2:0.3 Add NMP and mix, use a high-speed homogenizer to mix the above materials evenly to form a black paste with uniform color and high fluidity. MaterialThe black slurry was then coated on aluminum foil using a 150um four-sided preparation device, and the film was dried in a vacuum oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a punching machine, with metallic sodium as the counter electrode and 1 mol / L NaClO 4 EC+DEC (1:1 vol%) + 5% FEC was used as the electrolyte and the separator was a PP / PE / PP three-layer separator, which was assembled into a CR2016 button cell in a glove box.

[0065] The results in Table 1 show that the material has a discharge capacity of only 75.3 mAh / g at a rate of 0.1C (1C = 129 mAh / g), which is lower than that of the material in Application Example 2. The capacity is related to the phase purity of the material, indicating that the material may contain inactive sodium iron phosphate, sodium manganese phosphate or low-capacity sodium iron pyrophosphate, sodium manganese pyrophosphate and other impurities, thereby reducing the active ingredients in the material per unit mass, resulting in a decrease in the material capacity. This is mainly due to the anhydrous FePO4, Mn 2 O 3 This is caused by the uneven mixing of elements in the materials prepared as precursors. Table 1 shows that at a rate of 10C, the capacity retention rate of the electrode is only 79.2% compared with that at 0.1C. The low rate performance is related to the presence of a large number of grain boundaries between the impurity phase and the main phase, which hinders the sodium ion transmission process to a certain extent, resulting in a decrease in the rate performance of the material. At the same time, the larger number of pores in the particles will also hinder the diffusion of electrons, thereby affecting the rate performance of the material. Finally, at a rate of 1C, after 1000 cycles, the capacity retention rate of the electrode was only 90.2%, which was severely attenuated, indirectly reflecting the instability of the material structure. On the one hand, the reason comes from the different volume expansion rates of the main phase and the impurity phase, which leads to cracks at the crystal interface, and the continuous decomposition of the electrolyte destroys the interface structure of the material. On the other hand, the higher specific surface area of ​​the material will catalyze its reaction with the electrolyte at high voltage, resulting in problems such as dissolution of the interface and structural rockization, affecting the cyclic stability of the material. In summary, with anhydrous FePO4, Mn 2 O 3 Na prepared from precursor 4 Fe 1.79 Mn 1.12 (PO 4 ) 2 P 2 O 7 The inhomogeneity of material reaction caused by low phase purity will accelerate the degradation of the electrochemical performance of the material.

[0066] Table 1 Performance test results The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.

Claims

1. A precursor for a positive electrode material of a polyanion sodium ion battery, characterized in that: The precursor chemical formula is Na x M y H z O a (PO b ) c mH2O; Wherein M is a transition metal element Fe and / or Mn; the relationship between x, y, z, a, b, and c is x+3y+z-2a+5c-2b×c=0, and the value range of m is m≥0.

2. A method for preparing a precursor for a positive electrode material for a polyanion sodium ion battery, characterized in that The following steps are involved: S1. Preparation of precursor solution: mixing a transition metal source with an acid solution, adjusting the pH of the solution, promoting the dissolution of the transition metal, and generating a transparent solution; S2. Preparation of a pre-oxidation precursor solution: adding an oxidant to the above solution to oxidize the divalent metal ions in the solution into trivalent metal ions to generate a pre-oxidation precursor solution; S3、Na x M y H z O a (PO b ) c Preparation of mH2O precipitation: Add phosphorus source and sodium source to the above pre-oxidation precursor solution, and use alkaline compounds to adjust the pH of the solution, so that the transition metal ions in the solution form Na x M y H z O a (PO b ) c mH2O precipitation; S4, purification treatment: the above precipitate is separated from the solid and liquid, washed to obtain the polyanion type sodium ion battery positive electrode material Na x M y H z O a (PO b ) c mH2O precursor powder.

3. The method for preparing a precursor for a positive electrode material for a polyanion type sodium ion battery according to claim 2, characterized in that: In step S1, the pH range is ≤4; in step S3, the pH range is ≥3.

0.

4. The method for preparing a precursor for a positive electrode material for a polyanion sodium ion battery according to claim 2, characterized in that: In step S2, the molar amount of the added oxidant is 1.0-2.0 times the molar amount of the transition metal in the precursor solution.

5. The method for preparing a precursor for a positive electrode material for a polyanion sodium ion battery according to claim 2, characterized in that: In step S2, the oxidant is one or more of hydrogen peroxide, peracetic acid, ammonium persulfate, sodium hypochlorite, sodium percarbonate, sodium perborate, sodium permanganate, and chromic acid.

6. The method for preparing a precursor for a positive electrode material for a polyanion sodium ion battery according to claim 2, characterized in that: In step S3, the phosphorus source is one or more of a phosphate compound, a pyrophosphate compound, metaphosphoric acid, sodium metaphosphate, phosphorus pentoxide, polyphosphoric acid, and sodium polyphosphate; the phosphate compound is one or more of phosphoric acid, sodium phosphate and its acid derivatives, and ammonium phosphate and its acid derivatives; the pyrophosphate compound is one or more of pyrophosphoric acid, sodium pyrophosphate and its acid derivatives, and ammonium pyrophosphate and its acid derivatives.

7. The method for preparing a precursor for a positive electrode material for a polyanion type sodium ion battery according to claim 2, characterized in that: In step S3, the sodium source is an inorganic sodium-containing compound and / or an organic sodium-containing compound, the inorganic sodium-containing compound is one or more of sodium sulfate, sodium nitrate, and sodium chloride; the organic sodium-containing compound is one or more of sodium formate, sodium acetate, sodium citrate, sodium ascorbate, sodium carboxymethyl cellulose, sodium ethanol, and sodium phenol.

8. The method for preparing a precursor for a positive electrode material for a polyanion sodium ion battery according to claim 2, characterized in that: In step S3, the alkaline compound is a nitrogen-containing compound and / or a sodium-containing alkaline compound, the nitrogen-containing compound is one or more of ammonia water, aniline, and amines; the sodium-containing alkaline compound is one or more of sodium oxide, sodium citrate, sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium formate, and sodium acetate.

9. The precursor for the positive electrode material of a polyanion type sodium ion battery according to claim 2, characterized in that: In step S4, the solid-liquid separation method is one or more of centrifugation, filtration, filter pressing, and vacuum filtration, and the Na x M y H z O a (PO b ) c ·mH2O A combination of one or more methods to quickly remove free water on the surface.

10. The method for preparing a precursor for a positive electrode material for a polyanion sodium ion battery according to claim 2, characterized in that: In step S1, The transition metal source is one or more of a water-insoluble manganese source, a water-soluble manganese source, a water-insoluble iron source, and a water-soluble iron source; The water-insoluble manganese source is one or more of elemental manganese, manganese oxalate, manganese hydroxide, manganous anhydride, manganous anhydride, permanganous anhydride, manganese monoxide, manganese dioxide, manganese trioxide, and manganese tetraoxide; the water-soluble manganese source is one or more of manganese sulfate, manganese nitrate, manganese acetate, manganese chloride, manganese citrate, and manganese gluconate; The water-insoluble iron source is one or more of elemental iron, ferric oxalate, ferric oxide, ferrous oxide, ferrous oxide, ferrous hydroxide, and ferric hydroxide; the water-soluble iron source is one or more of ferric sulfate, ferric chloride, ferric acetate, ferric citrate, ferric nitrate, ferric gluconate, and ammonium ferrous sulfate; The acid solution is an inorganic acid and / or an organic acid; the acid solution is one or more of nitric acid, sulfuric acid, hydrochloric acid, perchloric acid, permanganic acid, hydrobromic acid, hydroiodic acid, sulfurous acid, phosphoric acid, oxalic acid, hydrofluoric acid, chromic acid, carbonic acid, silicic acid, nitrous acid, hydrosulfuric acid, hypochlorous acid, formic acid, acetic acid, propionic acid, citric acid, tartaric acid, malic acid, benzoic acid, salicylic acid, and succinic acid.

Citation Information

Cited By

  • Precursor for polyanionic sodium-ion battery positive electrode material and preparation method therefor

    WO2026081913A1